Dampak Abrasi Pulau Tiban, Desa Kartikajaya Kecamatan Patebon Kabupaten Kendal - Distira Andy Liawan; Mahmud Abdul Haris (Institut Teknologi Adhi Tama Surabaya, 2021)
In mid-2017 there was a fairly large storm on the north coast of Java which resulted in quite a large amount of coastal abrasion in the tourist attraction